Cross-Sectional Surveys of the Prevalence of Follicular Trachoma and Trichiasis in The Gambia: Has Elimination Been Reached? - Sarah E Burr; Ansumana Sillah; Anselme S Sanou; Anita C Wadagni; John Hart; Emma M Harding-Esch; Sarjo Kanyi; Robin L Bailey (Public Library of Science (PLoS), 2016)
BACKGROUND:The Gambia's National Eye Health Programme has made a concerted effort to reduce the prevalence of trachoma. The present study had two objectives. The first was to conduct surveillance following mass drug administrations to determine whether The Gambia has reached the World Health Organization's (WHO) criteria for trachoma elimination, namely a prevalence of trachomatous inflammation-follicular (TF) of less than 5% in children aged 1 to 9 years. The second was to determine the prevalence of trichiasis (TT) cases unknown to the programme and evaluate whether these meet the WHO criteria of less than 0.1% in the total population. METHODOLOGY/PRINCIPAL FINDINGS:Three cross-sectional surveys were conducted between 2011 and 2013 to determine the prevalence of TF and TT in each of nine surveillance zones. Each zone was of similar size, with a population of 60,000 to 90,000, once urban settlements were excluded. Trachoma grading was carried out according to the WHO's simplified trachoma grading system. The prevalence of TF in children aged 1 to 9 years was less than 5% in each surveillance zone at each of the three surveys. The prevalence of TT cases varied by zone from 0 to 1.7% of adults greater than 14 years while the prevalence of TT cases unknown to the country's National Eye Health Programme was estimated at 0.15% total population. CONCLUSIONS/SIGNIFICANCE:The Gambia has reached the elimination threshold for TF in children. Further work is needed to bring the number of unknown TT cases below the elimination threshold.